Riwayat gizi buruk masa lalu (stunted) tidak berhubungan dengan prestasi belajar siswa SD di Kabupaten Sikka Nusa Tenggara Timur - Tobianus Hasan; Mohammad Djuffrie; Indiria L. Gamayanti (Alma Ata University Press, 2014)
ABSTRACTBackground: The main nutritional problem existed in Sikka District was high prevalence of stunting in children (49.6%). Sikka District Health Office data at 2009 and 2010 confirmed that Mego Subdistrict was categorized as area in which the citizens (particularly infants) had high risk experiencing health and nutritionissues with percentage of 43.3 in 2009 and 42.3 in 2010. Elementary school student’s passing percentage at Mego Subdistrict in education year of 2009/2010 placed in rank of 15 of 21 subdistricts in Sikka District.Objectives: To determine the association between history of malnutrition (stunted) and academic achievement of elementary school students at Sikka District, NTT.Methods: This was an observational study with cross sectional study design. Sample of this research were 3rd grade elementary school students who met inclusive and exclusive criteria. Bivariate and multivariate analysis was used ini this research.Results: Research result showed that bivariatelly stunted condition affects study achievement (p=0.027). External factors affecting study achievement was mother’s education (p=0.001), father’s education (p=0.001) and child’s intelligence (p=0.027). Multivariatelly, most affective factor in student’s study achievement at Mego Subdistrict was parent’s education. The most dominant factor affecting elementary student’s study achievement was mother’s education (p=0.001).Conclusions: Most students suffering stunted had low study achievement (87.2%) and stunted had no significant relation to study achievement. Student’s study achievement was affected by parent’s education.KEYWORDS: stunted, study achievementABSTRAKLatar belakang: Masalah gizi utama yang ada di Kabupaten Sikka adalah tingginya balita dengan status pendek dan sangat pendek yang mencapai 49,6%. Data Dinas Kesehatan Kabupaten Sikka tahun 2009 dan 2010 menyatakan bahwa Kecamatan Mego dikategorikan sebagai wilayah dengan masyarakat terutama balita berisiko tinggi mengalami masalah kesehatan dan gizi dengan persentase 43,3 pada tahun 2009 dan 42,3 pada tahun 2010. Persentase kelulusan siswa SD di Kecamatan Mego pada tahun ajaran 2009/2010 menempati urutan ke-15 dari 21 kecamatan yang ada di Kabupaten Sikka.Tujuan: Untuk mengetahui hubungan antara status gizi masa lalu (stunted) dan prestasi belajar siswa SD Kecamatan Mego, di Kabupaten Sikka NTT.Metode: Jenis penelitian ini adalah observasional dengan rancangan penelitian cross sectional study dengan sample penelitian meliputi anak sekolah dasar (SD) kelas III yang memenuhi kriteria inklusi dan eksklusi.Hasil: Hasil penelitian menunjukan bahwa secara bivariat kondisi stunted mempengaruhi prestasi belajar (p=0,027), selain stunted, faktor luar yang mempengaruhi prestasi belajar adalah pendidikan ibu (p=0,001), pendidikan ayah (p=0,001) dan intelegensi anak (p=0,027) Secara multivariat yang paling mempengaruhi prestasi belajar siswa SD di Kecamatan Mego adalah pendidikan ayah dan ibu. Tetapi faktor yang paling dominan mempengaruhi prestasi belajar siswa SD hanya pendidikan ibu (p=0,001).Kesimpulan: Sebagian besar siswa yang menderita stunted memiliki prestasi belajar yang rendah (87,2%) dan stunted tidak memiliki hubungan yang signifikan dengan prestasi belajar. Prestasi belajar siswa dipengaruhi oleh pendidikan orang tua.KATA KUNCI: stunted, prestasi belajar